Christopher Philips, The Battle for Syria: International Rivalry in the New Middle East - Mr. Sajid Aziz (CISS Insight Journal, 2016)
Two months from now will mark the sixth anniversary of Syrian war. What started in March 2011 as a peaceful revolt against the government of Bashir al-Assad soon morphed into a macabre civil war. The light of dawn the peaceful protestors heralded turned into a night of chaos and blood. The devastating war has had a severe toll on Syrian people. Approximately half a million people are dead (though, one should be skeptical when quoting these figures given the level of propaganda, lack of physical access to journalists and difficultly to sift truth from unverified reports filed to satiate the need of incessant demand information from a war zone); close to five million have sought refuge outside the country and more than 6 million are internally displaced. The economy is devastated and thousands of civilians have lived for years under sieges of both government and rebel forces. The harrowing images coming from rebel-controlled eastern Aleppo are a testament of the brutality of war wrought on people. The moral outrage it has rightly evoked should not bar us from critically analyzing the war and discussing the role of internal and external factors that have contributed in the lengthening and lethality of the war.